Glyphosate exposure and GM seed rollout unequally reduced perinatal health - Emmett Reynier; Edward Rubin (Proceedings of the National Academy of Sciences, 2025)
The advent of herbicide-tolerant genetically modified (GM) crops spurred rapid and widespread use of the herbicide glyphosate throughout US agriculture. In the two decades following GM-seeds’ introduction, the volume of glyphosate applied in the United States increased by more than 750%. Despite this breadth and scale, science and policy remain unresolved regarding the effects of glyphosate on human health. We identify the causal effect of glyphosate exposure on perinatal health by combining 1) county-level variation in glyphosate use driven by 2) the timing of the GM technology and 3) differential geographic suitability for GM crops. Our results suggest the introduction of GM seeds and glyphosate significantly reduced average birthweight and gestational length. While we find effects throughout the birthweight distribution, low expected-weight births experienced the largest reductions: Glyphosate’s birthweight effect for births in the lowest decile is 12 times larger than that in the highest decile. Together, these estimates suggest that glyphosate exposure caused previously undocumented and unequal health costs for rural US communities over the last 20 years.